EFFECT OF USE OF COMPUTER SIMULATIONS ON STUDENTS’ ACHIEVEMENT IN BASIC SCIENCE IN ENUGU EDUCATION ZONE, NIGERIA (UNIZIK Journal of STM Education, 2025)
This research examined the effect of use of computer simulations in instructional delivery on students’ achievement in Basic science in Enugu Education Zone of Enugu state. The study was guided by two research questions and three null hypotheses. A pretest-posttest nonequivalent control group quasi-experimental design was employed. Population of the study consisted of all Junior Secondary School Two (JSS2) students enrolled in public secondary schools within the Enugu Education Zone, from which 120 students was sampled using purposive and random sampling techniques. Data were collected using the Basic Science Achievement Test (BSAT), which was validated by three experts. The reliability of the CAT was determined using the Kuder-Richardson Formula 20, resulting in a reliability coefficient of 0.84. The experimental group was taught specific Basic science concepts using Computer simulations, while the control group received instruction on the same concepts through the traditional lecture method (LM).  Data were analysed using mean, standard deviation, and analysis of covariance (ANCOVA). The results indicated that the use of computer simulation in instructional delivery significantly improved students' achievement compared to the lecture method. No significant influence of gender on students’ achievement in Basic science was observed. Based on these findings, it was recommended that schools should integrate computer simulations into teaching, particularly Basic science, to improve student performance through interactive, experiential learning.
Keywords: Achievement, Basic Science, Computer Simulations, Instruction